2011
DOI: 10.1002/ajmg.b.32003
|View full text |Cite
|
Sign up to set email alerts
|

Mutation screening of the HDC gene in Chinese Han patients with Tourette syndrome

Abstract: Tourette Syndrome (TS) is a complex neuropsychiatric disorder characterized by vocal and motor tics. While environmental causes have been proposed to play a role, genetic factors are believed to be the main determinants of the disorder and its clinical manifestations. Recently, a heterozygous W317X mutation in the histidine decarboxylase gene (HDC) was reported to be responsible for TS in a two-generation pedigree. To investigate whether the HDC gene play a role in TS in Chinese Han population, we performed ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…These findings therefore suggested a potential role for HDC deficiency in the pathophysiology of TS through impairment of histamine neurotransmission. However, the inheritance pattern in this family is uncommon for TS, and a mutation screening of Chinese Han patients did not support the link between the aforementioned gene and TS [76].…”
Section: Clinical Studiesmentioning
confidence: 56%
See 1 more Smart Citation
“…These findings therefore suggested a potential role for HDC deficiency in the pathophysiology of TS through impairment of histamine neurotransmission. However, the inheritance pattern in this family is uncommon for TS, and a mutation screening of Chinese Han patients did not support the link between the aforementioned gene and TS [76].…”
Section: Clinical Studiesmentioning
confidence: 56%
“…The hypothesis of an involvement of the histaminergic system in the pathogenesis of TS was also supported by a more recent report on single nucleotide polymorphisms in the HDC region that are associated with TS [78]. However, HDC mutations were not replicated in larger scale studies [76], suggesting that these genetic alterations may only be responsible for a subset of patients with TS. Interestingly, we have recently seen increasing consensus that TS is a heterogeneous condition from both the phenotypic and genotypic points of view.…”
Section: Promising Avenues For Researchmentioning
confidence: 89%
“…HDC variants found in individuals with Gilles de la Tourette Syndrome (TS) in previous studies are also shown. The triangle indicates the position of the originally described mutation that led to a premature termination codon (p. W317*, c.951G>A) in a family with TS,7 and the stars indicate the position of variants described in Chinese Han patients with TS (not predicted to result in amino acid changes) 9. Access the article online to view this figure in colour.…”
Section: Methodsmentioning
confidence: 99%
“…Since the original study that implicated HDC in TS aetiology, Lei et al 9 screened the HDC gene for exonic mutations in 100 Chinese Han patients with TS, and could only find three variants, not predicted to result in amino acid changes: a C>T intronic transition (IVS1 +52C>T), which did not affect the splicing site, a synonymous C>A transition (c.426C>A) in exon 4 and a synonymous G>A transition (c.1743G>A) in exon 12 9. The first genomewide association study for TS only produced a weak association signal close to the HDC gene (p value of 0.02 with rs7166052) 3.…”
Section: Introductionmentioning
confidence: 99%
“…An involvement of the histaminergic system in the pathogenesis of TS was also supported by a report on single-nucleotide polymorphisms (SNPs) in the HDC region that are associated with TS (Karagiannidis et al, 2013). However, a mutation screening of Chinese Han patients did not support the link between HDC and TS (Lei et al, 2011), suggesting that HDC mutations may only be responsible for a rare and very specific form of TS.…”
Section: Tourette's Syndrome (Ts)mentioning
confidence: 97%